Establishment and characterization of an immortalized epithelial cell line from human gallbladder - Wang, Ziyi; Wang, Shijia; Jia, Ziheng; Zhao, Yuhao; Yang, Mao; Yan, Weikang; Chen, Tao; Xiang, Dongxi; Shao, Rong; Liu, Yingbin (Frontiers in Oncology, 2022)
Background: Gallbladder is a digestive organ in charge of bile storage and release. Despite of the high universality of gallbladder benign diseases including cholelithiasis and the lethality of gallbladder cancer, it is surprised to notice the lack of basic gallbladder researching models. The lack of non-cancerous human gallbladder epithelial cell line impeded the gallbladder diseases bench studies including cholecystitis occurrence and cancer transformation. Here, we established and characterized one non-cancerous gallbladder epithelial cell line named L-2F7 from human gallbladder tissue. Methods: Cholecystitis tissue was collected and epithelial cells were enriched by CD326 positive magnetic cell sorting. The cells were immortalized by introducing human telomerase reverse transcriptase (hTERT) and Simian virus 40 large T antigen (LT-SV40) via lentivirus infection system. After limiting dilution culturing, single clones were screened by examining the epithelial markers including CK7, CK9 and CD326, during which L-2F7 clone was identified epithelial property. Then cell morphology, genomic features and proliferation were characterized and RNA-sequencing was performed to investigate the differential expression patterns of gallbladder cancer in cell line level. L-2F7 cells were also transplanted to Nude (nu/nu) mice to determine its tumorigenic capability. Results: We successfully identified one of single clones named L-2F7 which highly expressed epithelial markers CD326, CK7 and CK19. This cell line proliferated with doubling time of 23 hours and the epithelial morphology sustained over 30 passages following immortalization. L2-F7 was tested to possess highly experimental compatibility including efficient transduction. In the perspective of genome, this cell line exhibited distinct non-synonymous mutations relative to gallbladder cancer tissues. Viewing from transcriptome, L-2F7 showed differential non-cancerous gene expression patterns compared with other GBC cell lines, like KRAS pathway activation and estrogen response signaling. Although displaying unexpected mobility, L-2F7 cells barely possess capability to develop tumors. Conclusion: We developed a non-cancerous gallbladder epithelial cell line, offering an attractive system for the study of gallbladder cancer and other gallbladder-related disorders.